Quality Assurance Mechanisms as Tools to Achieve the Continental Education Strategy for Africa - Awaah, Fred; Okebukola, Peter; Shabani , Juma (West African Journal of Open and Flexible Learning, 2022)
Since its launch in 2016, the Continental Education Strategy for Africa (CESA) has witnessed great successes, with African educational stakeholders leveraging on its 13 clusters to ensure the transformation of the continent’s education in furtherance of the achievements of the AU Agenda 2063. Organisations such as the Association of African Universities, the International Network for Higher Education in Africa, and the European Union have held conferences to create awareness and find ways to achieve the aspirations of the CESA. Their initiatives have not been without challenges, especially in a key fundamental quality assurance area – academic corruption. This desk review examines the Continental Education Strategy for Africa from a quality assurance lens by establishing the hindrances that academic corruption poses or will pose to the achievement of the strategy within the Africa Higher Education Space (AHES). The study further argues that achieving the desire to use African human resources to achieve the continent’s educational aspirations will entail measures that will minimise all forms of academically dishonest practices within the AHES, especially amongst students, since inappropriate teaching methods lead to tendencies of cheating. In curbing this, the review argues for an African-born educational model that assures quality and can reduce academic dishonesty towards the achievement of the CESA.